Identification of a New Sequence-Specific Endonuclease, NgoII, from Neisseria gonorrhoeae - Clanton, David J. (1978)
A class II restriction endonuclease which recognizes the same nucleotide sequence as EndoR·HaeIII has been found in four of seven isolates of Neisseria gonorrhoeae tested.